Adaptacyjna filtracja w ubezpieczeniach - Michalski, Tomasz; Twardowska, Krystyna; Tylutki, Barbara (Adaptive Filtering Analysis in Insurance, 2006)
We apply the so-called Kalman filter technique to predict the number of claims for future periods and the total claim payments in the collective risk model in insurance problems. The methods, based on adaptive linear discrete filtration and its averaging procedure, were examined for the probability distributions appearing in insurance. We have used the method to predict the loss reserving in automobile insurance for the next successive quarters. We get a satisfactory result. The method proposed here allows us to predict and control not only the claim amounts and numbers of claims using the absolute or cumulative values but also the loss ratios, the burning costs, the level of the reserves for unpaid compensations, the level of the catastrophic reserves or premiums.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 216-230